(untitled) - Kajima, Morinosuke (Rutland, Vermont, 1968)
This book, based on many years' study of and participation in Japan's foreign affairs, fills the gap. This book is divided into two parts an analysis of Japan's diplomatic response to the successive problems she faced, and a historical survey of the events of the whole period. Dr. Kajima has drwn upon the publihed diplomatic documents of the Western Powers, as well as memoirs, biographical works, and contemporary.